Investigating the Narrative Structure in the Story of Little Prince by Antoine De Saint-Exupery according to Gerard Genette's theory - Shahen Jamal Majeed; Saleh Jebrael Saleh (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Antoine de Saint-Exupery (1900-1944) published Little Prince in 1943, the story of an actual incident, which includes a collection of notes left by Saint-Exupery from his life`s experiences and thoughts. The research method is based on Gerar Genette`s narrative theory. A fictional narrative is the sequence of events within the axis of time. In narration, there is a distinction between what actually happened (the content of the narrative) and how to narrate what happened (the form of the narrative). The narrator is the main character of the story. According to Genette`s opinions, the narrative can be matched in the fictional world and text-based narrative because the center of orientation focuses on the character-narrator. The type of narrative is in the form of a co-narrative. The narrator is a knowledgeable narrator who controls the story. Each story is told through one or more narrators, and according to Genette, the narrator can be examined in terms of the type of narrative and narrative of events within time in the form of order, continuity and frequency. The little Prince, based on Genette`s theory, has an order or few time ranges from the present to the back and front, aesthetic and artistic aspect, and the painting event has the highest frequency, and the stability of dynamics or the speed of the story has positive acceleration and, in some parts negative acceleration.